2016
DOI: 10.1186/s13395-016-0084-8
|View full text |Cite
|
Sign up to set email alerts
|

Alterations to mTORC1 signaling in the skeletal muscle differentially affect whole-body metabolism

Abstract: BackgroundThe mammalian target of rapamycin complex 1 (mTORC1) is a central node in a network of signaling pathways controlling cell growth and survival. This multiprotein complex integrates external signals and affects different nutrient pathways in various organs. However, it is not clear how alterations of mTORC1 signaling in skeletal muscle affect whole-body metabolism.ResultsWe characterized the metabolic phenotype of young and old raptor muscle knock-out (RAmKO) and TSC1 muscle knock-out (TSCmKO) mice, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 44 publications
(81 reference statements)
3
30
1
Order By: Relevance
“…The mTORC1 signaling pathway is considered as a nitrogen-sensing pathway regulating skeletal MPS (17) and the recent work by Guridi et al (18) confirms that regulation of mTORC1 determines lean body mass. Experimental and clinical studies have shown that essential amino acids, particularly leucine, activate the mTORC1 pathway and consequently stimulate MPS (12).…”
Section: Discussionmentioning
confidence: 94%
“…The mTORC1 signaling pathway is considered as a nitrogen-sensing pathway regulating skeletal MPS (17) and the recent work by Guridi et al (18) confirms that regulation of mTORC1 determines lean body mass. Experimental and clinical studies have shown that essential amino acids, particularly leucine, activate the mTORC1 pathway and consequently stimulate MPS (12).…”
Section: Discussionmentioning
confidence: 94%
“…TSCmKO mice are resistant to diet‐induced obesity whereas 4E‐BP1/2 DKO mice are more sensitive to diet‐induced obesity . Furthermore, RAmKO mice are also resistant to diet induced‐obesity . Altogether, this suggest that direct changes in mTORC1 complex core/activity and of its downstream targets (such as 4E‐BP proteins) share common mechanisms that control the expression of lipid metabolism genes.…”
Section: Discussionmentioning
confidence: 95%
“…Because skeletal muscle and adipose tissue accounts for, respectively, about 70% and 10% of insulin‐mediated glucose uptake, altered whole‐body glucose homeostasis in mTORmKOKI mice most likely results from their pronounced reduction in muscle and fat mass. These alterations might reflect the onset of myopathy‐associated metabolic complications that were observed in aged RAmKO mice …”
Section: Discussionmentioning
confidence: 99%
“…These alterations might reflect the onset of myopathyassociated metabolic complications that were observed in aged RAmKO mice. 76…”
Section: Juvenile Mtormkoki Mice Show Features Of Glycogenosis and MImentioning
confidence: 99%